Comparative Performance Analysis of Multilevel Image Watermarking Using Cryptographic Algorithm - Gautam, Pankaj; Pandey, Mahendra Kumar; Patsariya, Sanjay (International Journal of Computer Sciences and Engineering, 2019)
This paper presents the comparative performance analysis of multi-level image watermarking using cryptographic algorithm. The proposed technique has been implemented and compared with other image watermarking technique based on DWT-SVD. In both watermarking techniques, the cover image is decomposed into four sub bands (LL, LH, HL and HH) using DWT and thereafter SVD is applied to LL sub band. Both the watermarking techniques have also been compared. Performance of methodology is evaluated using different fidelity parameters .The experimental results show the effectiveness of hybrid image watermarking scheme.